2023
DOI: 10.1111/tpj.16407
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis cell suspension culture and RNA sequencing reveal regulatory networks underlying plant‐programmed cell death

Abstract: SUMMARYProgrammed cell death (PCD) facilitates selective, genetically controlled elimination of redundant, damaged, or infected cells. In plants, PCD is often an essential component of normal development and can mediate responses to abiotic and biotic stress stimuli. However, studying the transcriptional regulation of PCD is hindered by difficulties in sampling small groups of dying cells that are often buried within the bulk of living plant tissue. We addressed this challenge by using RNA sequencing and Arabi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…Further, the 24 h unique downregulated genes here were enriched in cell cycle related GO terms may underscore the requirement to manage cell division and cycle processes under stress. In fact, disruption of the cell cycle is associated with stress in Arabidopsis (Takahashi et al, 2019) and programmed cell death responses (Burke et al, 2023; Chen et al, 2017; Takahashi et al, 2019, Zebell & Dong, 2015). As plants actively respond to stress, cell cycle arrest is plausible, which minimises use of energy and resources and is potentially related to localized induction of programmed cell death and subsequent aerenchyma formation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the 24 h unique downregulated genes here were enriched in cell cycle related GO terms may underscore the requirement to manage cell division and cycle processes under stress. In fact, disruption of the cell cycle is associated with stress in Arabidopsis (Takahashi et al, 2019) and programmed cell death responses (Burke et al, 2023; Chen et al, 2017; Takahashi et al, 2019, Zebell & Dong, 2015). As plants actively respond to stress, cell cycle arrest is plausible, which minimises use of energy and resources and is potentially related to localized induction of programmed cell death and subsequent aerenchyma formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the metacaspase AtMC3 is involved in modulating vascular plasticity in response to drought (Pitsili et al ., 2023) and overexpressing this protease results in plants that are more tolerant to drought with no apparent negative effects on growth or yield. As different stresses elicit both common and distinct pathways for the regulation of PCD (Burke et al ., 2023), the coordination of cell death pathways in response to combinations of stresses, and to adverse conditions outside the laboratory, will be an exciting area for future studies and an excellent way to validate the impact of findings on how plant PCD is controlled in real‐world scenarios.…”
Section: A Vision For the Next Decade Of Plant Pcd Researchmentioning
confidence: 99%
“…Burke et al . (2023) compared the transcriptional response to three different PCD‐inducing treatments used in combination with three cell death inhibitors; this enabled inference of core‐ and stimuli‐specific gene regulatory networks and isolation of putative transcriptional regulators of PCD that were not previously explored in the context of cell death. Importantly, this study highlighted that, depending on the treatment used to induce cell death, cell cultures can mimic PCD induced by biotic interactions, abiotic stress, and even developmental programmes, and in this way facilitate comparisons between cell death occurring in different contexts.…”
Section: A Vision For the Next Decade Of Plant Pcd Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy plays a key role in the mobilization of reserves and, as a consequence, in the resistance of cells to stress factors [ 208 , 209 , 210 , 211 , 212 ]. Autophagy during the starvation of cell cultures, including A. thaliana [ 213 , 214 ] and N. tabacum [ 184 , 215 , 216 , 217 ], is studied intensively. It has been shown that cell starvation is characterized by high proteolytic activity.…”
Section: Carbon Starvationmentioning
confidence: 99%